Synthesis of zinc oxide-encapsulated poly(methyl methacrylate)-chitosan core-shell hybrid particles and their electrochemical property - Chayannan Petchthanasombat (2018)
The synthesis of hybrid materials possessing zinc oxide nanoparticles encapsulated in core-shell polymer particles having poly(methyl methacrylate) core and chitosan shell (PMMA-CS/ZnO) was carried out via an emulsifier-free emulsion polymerization. The ZnO nanoparticles modified by 3-(trimethoxysilyl)propyl methacrylate (TPMZnO) were first prepared before being charged to the polymerization system. The effects of polymerization time (from 2. h to 6. h) and the amount of TPMZnO added (0.018. g, 0.020. g, and 0.030. g) were studied. It was found that the polymerization time of 5. h yielded colloidally stable hybrid latex with% MMA conversion up to 90%. Moreover, the increase in the amount of TPMZnO resulted in a decrease in% MMA conversion from 90% to 80%. It was also found from TGA analysis that the amount of TPMZnO added affected the percentage of TPMZnO encapsulation. PMMA-CS/ZnO particles with the size ranging from 173 to 245. nm were observed by TEM. In addition, the PMMA-CS/ZnO hybrid latexes possessed high positive charges in the range of 40-51. mV. The electrochemical property of the electrodes fabricated from PMMA-CS/ZnO nanoparticles was illustrated by cyclic voltammetry. © 2011 Elsevier Inc.